Un-Locking Strategic Lock-Ins of Local Media: An Investigation of Local Media's Preferences towards Public Support for Strategic Innovation. Issue 3 (16th March 2021) - Wilczek, Bartosz; Stanoevska-Slabeva, Katarina; Kernbach, Kimberley; Meckel, Miriam
Abstract: Media practitioners and policy makers are calling for more public support to facilitate the digital transformation of local journalism. However, newer academic literature focuses on explaining why public support for local media has become a necessity from a market failure and societal point of view. Almost no attention is dedicated to the question which known public support instruments might be considered as helpful from the perspective of local media and their digital transformation strategies. Therefore, this study draws on strategic path dependence theory and investigates how local media's perceptions of innovation constraints (i.e., lock-in mechanisms), their innovation status (i.e., lock-ins) and their preferences for public support instruments to enable innovation (i.e., public un-lock mechanisms) differ depending on the type of strategy. Four strategies are compared: two content strategies (multimedia formats and artificial intelligence applications) as well as two commercial strategies (revenue diversification and digital payment models). Data about the four strategies are collected with an online survey of local media, which operate in the Swiss Canton of St. Gallen. The findings show significant differences between the investigated strategies and suggest a differentiated approach to public support of local media in the digital age.